Women receiving massive transfusion due to postpartum hemorrhage: A comparison over time between two nationwide cohort studies - Ramler, Paul I. (Acta Obstet Gynecol Scand, 2019)
INTRODUCTION: Incidence of massive transfusion after birth was high in the Netherlands between 2004 and 2006 compared with other high‐income countries. This study investigated incidence, causes, management and outcome of women receiving massive transfusion due to postpartum hemorrhage in the Netherlands in more recent years. MATERIAL AND METHODS: Data for all pregnant women who received eight or more units of packed red blood cells from a gestational age of 20 weeks and within the first 24 hours after childbirth, during 2011 and 2012, were obtained from a nationwide retrospective cohort study, including 61 hospitals with a maternity unit in the Netherlands. RESULTS: Incidence of massive transfusion due to postpartum hemorrhage decreased to 65 per 100 000 births (95% CI 56‐75) between 2011 and 2012, from 91 per 100 000 births (95% CI 81‐101) between 2004 and 2006, while median blood loss increased from 4500 mL (interquartile range 3250‐6000) to 6000 mL (interquartile range 4500‐8000). Uterine atony remained the leading cause of hemorrhage. Thirty percent (53/176) underwent peripartum hysterectomy between 2011 and 2012, compared with 25% (83/327) between 2004 and 2006. Case fatality rate for women who received massive transfusion due to postpartum hemorrhage was 2.3% (4/176) between 2011 and 2012, compared with 0.9% (3/327) between 2004 and 2006. CONCLUSIONS: The incidence of postpartum hemorrhage with massive transfusion decreased in the Netherlands between both time frames, but remained an important cause of maternal mortality and morbidity, including peripartum hysterectomy. National surveillance of maternal morbidity and mortality due to postpartum hemorrhage through an improved and continuous registration with confidential enquiries may lead to the identification of clear improvements of maternal care.